2019
DOI: 10.17219/dmp/103732
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the efficacy of three methods of delivering calcium hydroxide into the root canal

Abstract: Background. Calcium hydroxide, due to its favorable properties, such as an antimicrobial effect as well as its ability to dissolve necrotic tissues, inhibit tooth resorption and stimulate the formation of a hard tissue barrier, is widely used in root canal treatment. Objectives. The objective of this study was to compare the efficacy of 3 methods of delivery of calcium hydroxide into the canals. Material and methods. This in vitro experimental study was performed on acrylic resin blocks with simulated curved c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…This finding broadly supports the work of Rahde et al, who reported that the curvature did not influence the filling quality of Ca(OH) 2 into extracted human teeth [ 20 ]. However, conflicting results were reported by Sharifi et al, who found that the curvature affected the density of Ca(OH) 2 [ 9 ]. An explanation for this disparity could be the differences in experimental specimens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding broadly supports the work of Rahde et al, who reported that the curvature did not influence the filling quality of Ca(OH) 2 into extracted human teeth [ 20 ]. However, conflicting results were reported by Sharifi et al, who found that the curvature affected the density of Ca(OH) 2 [ 9 ]. An explanation for this disparity could be the differences in experimental specimens.…”
Section: Discussionmentioning
confidence: 99%
“…An explanation for this disparity could be the differences in experimental specimens. Sharifi et al used simulated canals in resin block to assess the effect of the canal curvature while Rahde used extracted human first molars and single-rooted teeth [ 9 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Several method have been employed for intra-canal Ca(OH) 2 placement, however, none of the studies have assessed method of placement three-dimensionally. [11][12][13][14][15][16][17][18][19][20] Hence, this study aimed to compare and evaluate the quality of three different method of intracanal placement of calcium hydroxide paste through CBCT.…”
Section: Introductionmentioning
confidence: 99%